2011
DOI: 10.1073/pnas.1111056108
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative phenotype in mice with a point mutation in transforming growth factor β type I receptor ( TGFBR1 )

Abstract: Regeneration of peripheral differentiated tissue in mammals is rare, and regulators of this process are largely unknown. We carried out a forward genetic screen in mice using N -ethyl- N -nitrosourea mutagenesis to identify genetic mutations that affect regenerative healing in vivo. More than 400 pedigrees were screened for closure of a through-and-through punch wound in the mouse ear. This led to the identification of a single pedigree with a heritable, fast, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
0
37
1
Order By: Relevance
“…3) identified a single point mutation in a TGFbR1. 63 This mutation resulted in enhanced TGFb signaling and a super-healer phenotype that epithelialized and healed faster with newly generated tissue rather than fibrosis. 63 In addition, embryonic fibroblasts from these mice had increased expression of a subset of TGFb target genes, confirming that the mutation, indeed, caused activation of the receptor and the TGFb signaling pathway.…”
Section: Tgfb Pathway In Tissue Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…3) identified a single point mutation in a TGFbR1. 63 This mutation resulted in enhanced TGFb signaling and a super-healer phenotype that epithelialized and healed faster with newly generated tissue rather than fibrosis. 63 In addition, embryonic fibroblasts from these mice had increased expression of a subset of TGFb target genes, confirming that the mutation, indeed, caused activation of the receptor and the TGFb signaling pathway.…”
Section: Tgfb Pathway In Tissue Regenerationmentioning
confidence: 99%
“…63 This mutation resulted in enhanced TGFb signaling and a super-healer phenotype that epithelialized and healed faster with newly generated tissue rather than fibrosis. 63 In addition, embryonic fibroblasts from these mice had increased expression of a subset of TGFb target genes, confirming that the mutation, indeed, caused activation of the receptor and the TGFb signaling pathway. 63 In contrast to these results, abrogation of TGFb1 signaling in TGFb1/ Rag2 double knockout mice resulted in improved closure of ear holes in comparison to wild-type or Rag2…”
Section: Tgfb Pathway In Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, a recent study has discovered a regenerative phenotype in mice with a point mutation in ALK5. 69 These mice display accelerated closure of ear punch wounds reminiscent of the perfect wound-healing response observed in ear punch wounds created in MRL/MpJ mice. 70 A preliminary study showed a small but significant acceleration in cutaneous (dorsal skin) wound closure in the ALK5 mutant mice, but the healing architecture and histological appearance did not markedly differ between ALK5 mutant and WT mice.…”
Section: Modulation Of Tgf-b Receptor Expressionmentioning
confidence: 99%
“…70 A preliminary study showed a small but significant acceleration in cutaneous (dorsal skin) wound closure in the ALK5 mutant mice, but the healing architecture and histological appearance did not markedly differ between ALK5 mutant and WT mice. 69 Further studies using these mice in incisional and excisional wound-healing models are needed to fully appreciate their potential for investigating TGF-b signaling dynamics in wound healing.…”
Section: Modulation Of Tgf-b Receptor Expressionmentioning
confidence: 99%